Dissection of Phenotypic and Genetic Variation of Drought‐Related Traits in Diverse Chinese Wheat Landraces. Issue 3 (1st November 2019) - Lin, Yu; Yi, Xin; Tang, Si; Chen, Wei; Wu, Fangkun; Yang, Xilan; Jiang, Xiaojun; Shi, Haoran; Ma, Jian; Chen, Guangdeng; Chen, Guoyue; Zheng, Youliang; et al.
Abstract : Core Ideas: Variations in 16 seedling traits under normal and drought conditions were investigated. Extremely resistant and sensitive accessions were identified for future analyses. Under normal and drought conditions, 57 and 29 QTL were identified, respectively. A total of 77 candidate genes were identified, and four were validated by qRT‐PCR. Drought is one of the most important abiotic stressors affecting wheat ( Triticum aestivum L.) production. To improve wheat yield, a better understanding of the genetic control of traits governing drought resistance is paramount. Here, using 645 wheat landraces, we evaluated 16 seedling traits related to root and shoot growth and water content under normal and drought (induced by polyethylene glycol) conditions. Extremely resistant and sensitive accessions were identified for future drought‐resistance breeding and further genetic analyses. A genome‐wide association study was performed for the 16 traits using 52, 118 diversity arrays technology sequencing (DArT‐seq) markers. A total of 57 quantitative trait loci (QTL) were detected for seven traits under normal conditions, whereas 29 QTL were detected for eight traits under drought conditions. On the basis of these markers, we identified 56 candidate genes for six seedling traits under normal conditions, and 21 candidate genes for seven seedling traits under drought conditions. Four candidate genes were validated under normal and drought conditions using quantitative reverse transcription polymerase chain reaction (qRT‐PCR) data. The co‐localization of the flowering date and drought‐related traits indicates that the regulatory networks of flowering may also respond to drought stress or are associated with the correlated responses of these traits. The phenotypic and genetic elucidation of drought‐related traits will assist future gene discovery efforts and provide a basis for breeding drought‐resistant wheat cultivars.